Personal carbon trading: Notional concept or workable proposition? Exploring theoretical, ideological and practical underpinnings - Gill Seyfang; Irene Lorenzoni; Mike Nye (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2007)
To effectively mitigate climate change in the long-term, limiting carbon dioxide emissions at the individual level has been proposed. Known as personal carbon allowances, these would be decreased year-on-year. Trading in personal carbon allowances would be encouraged, as a means to effectively and equitably reduce emissions overall. This conceptual paper aims to critically examine personal carbon trading (PCT) by questioning the assumptions underlying this proposal and identifying the gaps in current thinking. The paper first discusses the origin and development of the PCT idea, identifies key players and proponents of the proposal, and examines its economic basis as a market instrument. Drawing on lessons from several related areas of experience (the EU Emissions Trading System, voluntary Carbon Rationing Action Groups, and Complementary Currencies), these are used to examine likely success factors and inform future policy and implementation of PCT. A set of four critical issues are identified, which straddle political, social, economic, environmental, cultural and ethical domains, and which demand greater attention before the PCT idea can be progressed.
Keywords: 330; carbon management; climate change; mitigation; Personal carbon allowances; policy; Emissionshandel; Klimaveränderung